2016
DOI: 10.1139/cjfr-2016-0113
|View full text |Cite
|
Sign up to set email alerts
|

Broad-scale distribution of epiphytic hair lichens correlates more with climate and nitrogen deposition than with forest structure

Abstract: Hair lichens are strongly influenced by forest structure at local scales, but their broad-scale distributions are less understood. We compared the occurrence and length of Alectoria sarmentosa (Ach.) Ach., Bryoria spp., and Usnea spp. in the lower canopy of > 5000 Picea abies (L.) Karst. trees within the National Forest Inventory across all productive forest in Sweden. We used logistic regression to analyse how climate, nitrogen deposition, and forest variables influence lichen occurrence. Distributions overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Alectoria , with an incomplete circumpolar distribution and an oceanic tendency (Ahlner, 1948), peaks in old, humid boreal forests in Fennoscandia (Esseen et al., 2016). Bryoria and Usnea are circumpolar species that grow on a wide range of tree species (Thell & Moberg, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alectoria , with an incomplete circumpolar distribution and an oceanic tendency (Ahlner, 1948), peaks in old, humid boreal forests in Fennoscandia (Esseen et al., 2016). Bryoria and Usnea are circumpolar species that grow on a wide range of tree species (Thell & Moberg, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…They constitute an important diet of reindeer, caribou and other mammals (Hauck, 2011) and provide shelter for invertebrates, including high-quality prey for passerine birds (Pettersson et al, 1995). These lichens die or suffer from air pollutants (Bruteig, 1993;Johansson et al, 2010) and from other global change factors (Esseen et al, 2016;Nascimbene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study exploring the species-elevation relationship of epiphytic lichens in spruce forests of the Alps [39] stresses the sensitivity of hair-lichens to both increased temperature and precipitation. On a broader scale, Essen et al [41] demonstrated that climate and nitrogen deposition are the main factors shaping the distribution of hair-lichens; their effects are greater than the response to forest structures. Hair-lichens have a high surface area to biomass ratio [25] and, in high-elevation forests, are physiologically active most of the year [42].…”
Section: Lichen-climate Relationships With Emphasis On Hair-lichensmentioning
confidence: 99%